THE SHRINK FIT WITH ELASTIC-PLASTIC HUB EXHIBITING VARIABLE THICKNESS - GUVEN, U (SPRINGER-VERLAG WIEN, 1991)
An analytical solution for a shrink fit consisting of an elastic disk with constant thickness and partially plasticized hub with variable thickness is presented. The analysis is based on Tresca's yield condition, its associated flow rule and linear strain hardening.
Keywords: Mechanics